CHARACTER MOTIVE IN JAKARTA JINGGA NOVEL BY RIA N. BADARIA - Mayanda, Sri Anisa; Rahmat, Wahyudi; Satini, Ria (Magistra Andalusia: Jurnal Ilmu Sastra, 2019)
This research is motivated by which forms of character motifs in the Jakarta Jingga Karya Ria N novel in interacting. Motive is one of the reasons or encouragement of people to behave in certain ways. So in this research, focus on the shape of the character's motives in this novel. The purpose of this research is to describe the motifs of the characters in the Jakarta Jingga Karya Ria N. Badaria novel. This motif uses Maslow's theory (in Sobur 2013: 274). This type of research is qualitative. The method in this research is content analysis. The data used in this study are quotes related to character motifs in the Jakarta Jingga novel by Ria N. Badaria, while the data source in this study is the Jakarta Jingga Karya Ria N. Badaria novel. Data analysis techniques in this study are, describing the data based on character motifs. The findings contain five types of character motifs in the Jakarta Jingga Karya Ria N. Badaria novel. First, physiological motives. Second, the motive for feeling safe. Third, love and motives that are already owned. Fourth, the motif of appreciation. Fifth, self-actualization motives.